Employment in Informal Sector of Russia: Unemployment and Other Socio-Economic Factors - Sergey V. Kiselev; Sanat K. Seitov; Valery A. Samsonov; Ilya V. Filimonov (Население и экономика)
In Russia in 2023, 18.3% of the employed were engaged in the informal sector. As in many other countries, the informal economy is important for the social and economic situation of the population. This paper aims to identify the impact of specific key factors, such as unemployment rate, wages, poverty level, number of formal sector actors, proportion of the rural population, on the proportion of the informally employed. The Two-Stage Least Squares Method estimates allow to conclude that wages and the number of formal sector actors had a negative effect on the proportion of the informally employed in Russia in 2009–2021, while the unemployment rate had a positive effect. The paper shows a lack of statistical significance of the impact of the proportion of the rural population on the proportion of the informally employed.